Stimulating sustainable energy at maritime ports by hybrid economic incentives: A bilevel optimization approach - Molavi, Anahita; Lim, Gino J.; Shi, Jian (Applied energy, 2020)
•Develops a novel hybrid economic approach to stimulate sustainable energy at maritime ports.•Enables the co-operation of different stakeholders of port energy systems.•Case studies offer insights into mitigating emissions while satisfying port energy demand. Over the past few decades, maritime ports have faced ever-increasing critiques regarding their significant production of air emissions resulting from their energy activities. To promote sustainability at ports, regulatory authorities have introduced the concept of regulations and economic incentives. In this paper, we analyze the process in which a regulatory authority defines regulations, incentives, and tax policies to motivate one or more ports in the region to initiate energy sustainability and emission-reduction efforts. We model the behaviors of both the regulatory authority and the participating ports in the form of a multi-objective mixed-integer nonlinear bilevel optimization problem to capture the hierarchy of the policy-making process and the existing competitions among the ports. The proposed model finds the optimal incentive and tax policies for the policy-maker in the upper-level and provides the ports in the region with the optimal choice of sustainable energy solutions and service prices in the lower-level. Simulation results show that the proposed approach can effectively reduce the region-wide emission from the port activities while ensuring port entities’ welfare, competitiveness, and sustainable growth as regional energy hubs.